New-born baby naming practices of the Vhavenḓa: A sociolinguistic analysis perspective. Issue 2 (3rd July 2019) - Mahwasane, Mutshinyani Mercy; Tshifaro, Thambatshira Johannes
Abstract : The naming of a new-born baby plays a very important role in all cultures around the world, including the Vhavenḓa community. According to Tshivenḓa culture, the paternal grandparents and other senior members, as custodians of culture, are vested with the power to name new-born babies. Name-givers convey inherent communicative messages through these names, such as mocking, scolding and instigating conflicts which tend to cause heated discourse that becomes a battlefield for the name-givers and addressees. This practice is met with resistance from younger parents who now tend to take the responsibility of naming their own babies. Ethnography of communication, and critical discourse analysis (CDA) theories are utilised to investigate the Tshivenḓa new-born baby naming practices, which have undergone significant changes over time. The CDA model sheds light on how power relations play out, and ethnography of communication focuses on the appropriateness and effectiveness of the meanings of names with regard to the identity of the children. This study is a descriptive survey design and utilised questionnaires and interviews as the primary sources in gathering data. So far, little research has been conducted on Vhavenḓa new-born baby naming practices, as far as can be ascertained.